The Philosophical Apologetics of the Cambridge Platonists - Raube, Sławomir (Folia Philosophica, 2000)
The present article shows the philosophy of the 17th c. Platonists in Cambridge through their main interest, namely the problem of atheism and „atheistic motifs” in the texts. This is why the philosophical reflection of the English Platonists is so clearly dominated by the spirit of apologetics. Atheism was, however, for Cudworth and other Cambridge Platonists not only a question pertaining to purely philosophical controversies. The English Platonists, who, at the same time, were Anglican clergymen, perceived atheism also a threat to the social order, for the atheistic, or nearly atheistic, concept of the state, such as the one put forward by T. Hobbes, undermined from their point of view, the very foundation of the public order which they saw in the religiously motivated morality and individual conscience. A description and analysis of atheism is therefore the most important of the Cambridge philosophers’ achievements.